3D SIMULATION STUDY OF INHOMOGENEOUS MICROSTRUCTURE AND ITS EVOLUTION (advantages of visual simulation technique in stereological analysis) - Song, Xiaoyan; Rettenmayr, Markus; Liu, Guoquan (Image Analysis and Stereology, 2011)
A 3D Monte Carlo technique has been used to simulate a complex process of recrystallization in a material containing precipitates after graded deformation. By the simulation model, the inhomogeneous deformed microstructure and its evolution during subsequent annealing were directly displayed; moreover, the locally varying recrystallized microstructure was quantitatively analyzed. The simulation results were well verified by experiments with an aluminum alloy containing Al3Zr particles that had been subjected to deformation and annealing for recrystallization. In the stereological analysis of a non-random microstructure and its evolution kinetics, the visual simulation technique showed apparent advantages for sampling, detection and measuring.